2018
DOI: 10.1080/15374416.2017.1417860
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Parent-Reported ADHD Diagnosis and Associated Treatment Among U.S. Children and Adolescents, 2016

Abstract: The purpose of this study is to estimate the national prevalence of parent-reported attention deficit/hyperactivity disorder (ADHD) diagnosis and treatment among U.S. children 2-17 years of age using the 2016 National Survey of Children's Health (NSCH). The NSCH is a nationally representative, cross-sectional survey of parents regarding their children's health that underwent a redesign before the 2016 data collection. It included indicators of lifetime receipt of an ADHD diagnosis by a health care provider, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

46
578
13
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 877 publications
(693 citation statements)
references
References 33 publications
46
578
13
9
Order By: Relevance
“…2,3 Psychiatric comorbidities are also common and are associated with adverse effects including greater disability and increased risk for persistence of headache into adulthood. 8,9 Given the high prevalence and the associated health consequences, headache in childhood may result in substantial economic costs to families, healthcare systems, and society. 7 Youth with headache are more likely to have at least 1 of these psychiatric comorbidities than the general population of youth in the United States, where prevalence estimates are 7.1% for anxiety disorders, 3.2% for depressive disorders, and 9.4% for ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Psychiatric comorbidities are also common and are associated with adverse effects including greater disability and increased risk for persistence of headache into adulthood. 8,9 Given the high prevalence and the associated health consequences, headache in childhood may result in substantial economic costs to families, healthcare systems, and society. 7 Youth with headache are more likely to have at least 1 of these psychiatric comorbidities than the general population of youth in the United States, where prevalence estimates are 7.1% for anxiety disorders, 3.2% for depressive disorders, and 9.4% for ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Rates of ADHD diagnoses in preschoolers, recently estimated to be 2.1%, are lower than that of school-age children and adolescents (Danielson et al, 2018). Nevertheless, in this age group the frequency of ADHD diagnosis has been rising, more than doubling between 2007/2008 and 2016 (Danielson et al, 2017(Danielson et al, , 2018. These findings are consistent with insurance claims data from 2008 to 2014 that indicate increases in the proportion of 2-5 year-old children being assessed and/or treated for ADHD (Visser et al, 2016).…”
Section: Introductionmentioning
confidence: 85%
“…Additionally, behavioral interventions, relative to pharmacological treatments, may differentially impact proximal outcomes, such as parent competence and mental health (Rajwan, Chacko, & Moeller, 2012). A recent population survey in the United States indicated that, compared to school-age children, a significantly lower proportion of preschoolers with ADHD were being treated with medication (68.6% vs. 18.2%), although the proportion treated with behavioral interventions did not differ significantly between the age groups (51.4% vs. 59.5%; Danielson et al, 2018). A recent population survey in the United States indicated that, compared to school-age children, a significantly lower proportion of preschoolers with ADHD were being treated with medication (68.6% vs. 18.2%), although the proportion treated with behavioral interventions did not differ significantly between the age groups (51.4% vs. 59.5%; Danielson et al, 2018).…”
Section: Treatmentmentioning
confidence: 99%
“…It is worth alerting to this ready association of ADHD with medication, as opposed to nonmedical treatment. Danielson et al () reported that medication is still the most used treatment for ADHD (62.0% of children with ADHD), pointing out that more than half of the children with ADHD do not receive behavioral treatment. Vereb and DiPerna () describe a lack of knowledge about alternative treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, a large and controversial increase in Attention Deficit/Hyperactivity Disorder (ADHD) medication use by children has been observed in many studies worldwide. In the United States, an estimated 8.4% of children received stimulant medication in 2016 (Danielson et al, ), up from 2.4% in 1996 to 3.5% in 2008. In the UK, the prevalence of ADHD drug use in children under 16 increased 34‐fold overall, rising from 0.02% in 1995 to 0.51% in 2008 and then stabilized (Beau‐Lejdstrom, Douglas, Evans, & Smeeth, ).…”
Section: Introductionmentioning
confidence: 99%